The development of a novel sperm washing medium, enriched with serotonin as the active constituent, with the objective of enhancing sperm motility and viability - Yilmazer, Y.; Cetin, F.; Moshfeghi, E.; Dogan, S.; Aydin, T. (OXFORD UNIV PRESS, 2024)
40th Hybrid Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology, Amsterdam, NETHERLANDS, JUL 07-10, 2024